Persona 5. Vol. 5 - Murasaki, Hisato (VIZ Media LLC, 2021)
"Based on the popular video game, this manga's phantom thieves will steal your heart. After being arrested and having to transfer to a new high school in Tokyo, Akira Kurusu is given the goal of rehabilitation and awakened to a new power--the power of one's true self, a Persona.sona."--Provided by publisher.